Os sentidos da participação social no Programa Dinheiro Direto na Escola (PDDE): trajetórias no contexto da racionalidade neoliberal - Nogueira, Renan Moreira (2022)
This evaluative research on the design of Money Direct into The School Program (PDDE) is focused on its participative dimension, inspired by post-positivists frameworks, such as Rodrigues (2008; 2011; 2016; 2019), Lejano (2012), and Gussi (2008). This qualitative research tries to interpret the senses of social participation as a political dimension of PDDE in a context of neoliberal rationality. The research's locus is the middle-level bureaucracy (LOTTA; PIRES; OLIVEIRA, 2014) of the National Development of Education Fund (FNDE), PDDE's implementation organization. The corpus is formed by the analysis of documents, literature review, and in-depth interviews, using Text Discursive Analysis methodology (MORAES e GALIAZZI, 2016), which have composed the topics of content, context, and institutional trajectory analysis with the goal to accomplish an evaluative synthesis of the program. The results demonstrate that PDDE is solidly institutionalized, to what the fighting of the interviewed subjects has contributed to. The program has created a wide communication network between the Federal Government and public schools and has shared power with schools in the public funding game, but it still concentrates the discourses on its socioeconomic dimension, that, beyond being insufficient, in a context of permanent difficulties of public education funding, shades its political dimension. Participation still relies on the democratic characteristics of each institution where the policy runs through and it is perceived by middle bureaucrats as a horizon, a culture still to be created, although not set as a high priority in the data that was analyzed. This participation is problematized with the concept of neoliberal rationality (BROWN, 2017), which perverts its democratic senses.